The Effect of Capital Intensity and Inventory Intensity on Tax Aggressiveness in Multinational Companies in the Manufacturing Sector Listed on the IDX - Shelma Adiel Anindya; Eni Srihastuti; Imarotus Suaidah (LP2M IAIN Palopo, 2026)
This study investigates the influence of capital intensity and inventory intensity on tax aggressiveness among multinational corporations in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024, using the effective tax rate (ETR) as a proxy for tax aggressiveness. The approach employed is associative quantitative research based on panel data from 14 companies with a total of 70 observations selected through purposive sampling, processed employing multiple linear regression analysis via IBM SPSS 29. The test results indicate that capital intensity has a positive and significant effect on ETR (coefficient +0.038), this indicates that a higher proportion of fixed assets relative to total assets is associated with an increase in the company’s reported ETR, suggesting a lower level of tax aggressiveness This finding is inconsistent with the depreciation shield hypothesis and suggests that in the context of multinational manufacturing companies, investment in fixed assets tends to be accompanied by tax compliance burdens that actually increase ETR. Conversely, inventory intensity has a negative and significant effect on ETR (coefficient −0.151), meaning that the higher the proportion of inventories to total assets, the lower the ETR reported, which reflects an increase in tax aggressiveness. This finding indicates that in multinational manufacturing companies, intensive inventory management has the potential to suppress taxable income through storage costs, inventory valuation, and cross jurisdictional supply chain mechanisms. The findings suggest that both variables jointly have a significant effect on tax aggressiveness, with the regression model explaining 32.1% of the changes in tax aggressiveness. These findings validate that the characteristics of multinationality including international compliance pressures and consolidated accounting standards shape tax behavior that differs from domestic manufacturing companies, while also implying the need for a tax oversight approach based on asset structure profiling for multinational entities.